2015
DOI: 10.1007/s11356-015-4601-9
|View full text |Cite
|
Sign up to set email alerts
|

New isotopic evidence of lead contamination in wheat grain from atmospheric fallout

Abstract: Crops could accumulate trace metals by soil-root transfer and foliar uptake from atmospheric fallout, and an accurate assessment of pollution sources is a prerequisite for preventing heavy metal pollution in agricultural products. In this study, we examined Pb isotope rates to trace the sources of Pb in wheat grain grown in suburbs. Results showed that, even in zones with scarcely any air pollution spots, atmospheric fallout was still a considerable source of Pb accumulation in wheat. The concentration of Pb i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This implies that total soil Pb should not be used as a predictor for wheat Pb accumulation in these soils. Earlier research suggested that, in areas where atmospheric Pb deposition occurs, wheat grain Pb is mainly attributed to leaf absorption of Pb particulates (Douay et al., 2008; Ma, Liu, Hu, et al., 2019; Ma, Liu, Jin, et al., 2019; Yang et al., 2015). The Pb atmospheric deposition in the study area was previously determined to be ∼100 mg (m 2 30 d) −1 , which is much greater than “cleaner” areas (Qiu et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that total soil Pb should not be used as a predictor for wheat Pb accumulation in these soils. Earlier research suggested that, in areas where atmospheric Pb deposition occurs, wheat grain Pb is mainly attributed to leaf absorption of Pb particulates (Douay et al., 2008; Ma, Liu, Hu, et al., 2019; Ma, Liu, Jin, et al., 2019; Yang et al., 2015). The Pb atmospheric deposition in the study area was previously determined to be ∼100 mg (m 2 30 d) −1 , which is much greater than “cleaner” areas (Qiu et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Unsafe heavy metal concentrations in wheat grain, with respect to human consumption, have been reported (Douay et al, 2008;Huang et al, 2008;Li et al, 2020b;Liu et al, 2017;Liu, Cui, et al, 2020;Ma et al, 2015;Rezapour et al, 2019). Because wheat is an important worldwide food source (Senapati & Semenov, 2020;Wu et al, 2020), elevated heavy metal concentrations in wheat grain imply that human health may be adversely affected.…”
Section: Health Risk Of Consumption Of Wheat Grain From the Polluted mentioning
confidence: 99%
See 1 more Smart Citation
“…Cu, Zn, Pb, and Cd exhibited good correlations between grains and soils, soils and roots with the exception of Zn in grains and soils. It has been known that generally these elements in wheats came mainly from soils (Wang et al, 2012b;Çıçek et al, 2013;Wahsha et al, 2014;Safari et al, 2015) although few studies reported that Pb accumulation in wheat samples was mainly contributed by atmospheric deposition, rather than the contaminated soil (Yang et al, 2015). The significant correlations for Hg were only found between soils and roots, stems and leaves, and leaves and shells.…”
Section: Principal Source Of Hg In Wheatsmentioning
confidence: 97%
“…The toxicity of metals is the result of their binding to important enzyme systems in the animal cell or to certain components of the cell membrane. Human exposure to potentially toxic metals is mainly through food (4,7,9,10,12,20,21,30). Potentially toxic metals end up in food in multiple ways: along with raw materials, following treatments applied in agriculture, during processing, storage and transport, from auxiliary materials, from water used in technological processes, etc.…”
Section: Introductionmentioning
confidence: 99%